KOALISI DAN PENGELOLAAN KOALISI, PADA PEMERINTAHAN JOKO WIDODO-JUSUF KALLA - Efriza Efriza (Universitas Nasional, 2018)
This paper discusses the relationship between the President and the House of Representatives and the coalition government based on the three years of President Joko Widodo (Jokowi), who was trapped in inter-institutional competition as a consequence of a mixture of presidential and multi-party systems.Initialy, President Jokowi has the desire to realize a coalition based on ideology and the same program (consensus coalition) between political parties, but the reality, it is difficult to make it happen in government, finally President Jokowi re-elected a coalition of “all parties”. Using some of the basics of Scott Mainwaring and David Altman about presidential and multiparty combination systems and coalitions in presidential systems, complemented by several Coalitions. Then, complete the results of Otto Kirchheimer on Catch All Party, to outline the transformation of the party in this modern era. Accompanied by discussions on political parties in Indonesia, based on Yasraf Amir Piliang's description of political nomadism. Based on the facts and outcomes, a combination of presidential and multiparty systems and the government's management of government by President Jokowi, which manages a